The mediating effects of resilience on technostress creator and employee’s well-being in financial industries within Klang valley - Mokhtar, Aflinda; Mohamad Yunus, Noor’ain (Universiti Teknologi Mara Selangor, 2024)
The rapid advancement of technology has led to the emergence of technostress, a significant issue in organizations, particularly among technology-illiterate employees. The financial industry, in its quest for operational efficiency, has embraced information and communication technologies (ICTs) extensively. While these technologies have brought about numerous benefits, they have also given rise to technostress, a phenomenon that can adversely affect employee well-being. This study is significant as it examines the mediating role of resilience in the relationship between technostress creators and employee well-being within the financial industry. The study will be conducted in the financial industry, a sector that has been particularly impacted by the rapid digitalization of business processes and the increased reliance on technology. The findings of this study will contribute to the existing literature on technostress and employee well-being by providing empirical evidence on the role of resilience in mitigating the adverse effects of technostress. Additionally, the study's implications will offer practical insights for organizations in the financial industry to develop and implement strategies that promote employee resilience, thereby enhancing their overall well-being and productivity.